In Working Progress - Goetschmann, Alexandre; Davidi, Guy (Israel, 2005)
West from Ramallah a new city is under construction: Kiriyat Sefer. In the early hours of the morning, the construction workers from a neighboring Palestinian village, Bilin, walk to work. Unemployed since the early days of the Second Intifada and drowned into financial debts, Maher Hatib also works in the new settlement that is being built. One day in the lives of the Palestinian construction workers trapped between their need to survive and the ambiguity of their work.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films